Hydrogen embrittlement behaviors of ultrafine-grained 22Mn–0.6C austenitic twinning induced plasticity steel. Issue 24 (20th September 2017) - Bai, Yu; Tian, Yanzhong; Gao, Si; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract: Abstract : Hydrogen embrittlement behaviors of a 22Mn–0.6C (mass%) twinning induced plasticity (TWIP) steel with the grain sizes of 21 μm (coarse grain) and 0.58 μm (ultrafine grain) were investigated by means of hydrogen precharging and subsequent slow strain rate tensile tests. The total elongation and fracture stress for both of the coarse-grained and ultrafine-grained specimens decreased by hydrogen charging. The area fraction of the brittle fracture surfaces in the ultrafine-grained specimen was much smaller than that in the coarse-grained specimen. Three-point bending test also showed that the reduction of the fracture toughness by the introduction of hydrogen was much smaller in the ultrafine-grained specimen than that in the coarse-grained specimen. It was concluded that the suppressed hydrogen embrittlement by grain refinement in the 22Mn–0.6C TWIP steel was probably due to the smaller hydrogen contents per unit grain boundary area in the finer grain-sized material.